A Two-level Coordination Strategy for Distribution Network Balancing - Cui, Xueyuan; Ruan, Guangchun; Vallee, Francois; Toubeau, Jean-Francois; Wang, Yi (IEEE transactions on smart grid, 2024)
Uncertain distributed energy resources and uneven load allocation cause the three-phase unbalance in distribution networks (DNs), which may harm the health of power equipment and increase the operational cost. There are emerging opportunities to balance three-phase DNs with a number of power electronic devices installed in the system. In this paper, we propose a novel two-level coordination strategy to improve the network balancing performance, where soft open points (SOPs) and phase switch devices (PSDs) are hierarchically coordinated in the network. At the upper level, a new type of SOPs with the function of phase switching is designed to explore the cross-phase power transfer ability; at the lower level, PSDs are utilized to flexibly allocate individual loads to specific phases. The two-level coordination strategy is typically formulated as a mixed-integer nonlinear programming (MINLP) problem. To solve the model accurately and efficiently, we develop a successive linearization algorithm to approximate it to a mixed-integer linear programming (MILP) problem at each iteration. On this basis, we propose a heuristic time-independent fixing algorithm to further ease the computational burden by eliminating a large number of integer variables in the MILP problem. Numerical simulations are conducted to validate the effectiveness, accuracy, and efficiency of the proposed method.